Localization and developmental expression of two chicken host defense peptides: cathelicidin-2 and avian β-defensin 9. (August 2016) - Cuperus, Tryntsje; van Dijk, Albert; Dwars, R. Marius; Haagsman, Henk P.
Abstract: In the first weeks of life young chickens are highly susceptible to infectious diseases due to immaturity of the immune system. Little is known about the expression of host defense peptides (HDPs) during this period. In this study we examined the expression pattern of two chicken HDPs, the cathelicidin CATH-2 and the β-defensin AvBD9 by immunohistochemistry in a set of organs from embryonic day 12 until four weeks posthatch. AvBD9 was predominantly found in enteroendocrine cells throughout the intestine, the first report of in vivo HDP expression in this cell type, and showed stable expression levels during development. CATH-2 was exclusively found in heterophils which decreased after hatch in most of the examined organs including spleen, bursa and small intestine. In the lung CATH-2 expression was biphasic and peaked at the first day posthatch. In short, CATH-2 and AvBD9 appear to be expressed in cell types strategically located to respond to infectious stimuli, suggesting these peptides play a role in embryonic and early posthatch defense. Highlights: Chicken cathelicidin-2 protein is exclusively expressed in heterophils. Heterophil numbers decrease posthatch in spleen, bursa and small intestine. Avian β-defensin 9 is expressed in enteroendocrine cells of the intestine. Avian β-defensin 9 protein is constitutively expressed during development.